Quick Response Code Technology-based Contact Tracing Solutions to Mitigate Epidemic Outbreaks: A Review - Agburu O. Adikpe; Ezekiel E. Agbon; Abdulkadir M. Giwa; Habib T. Adeyemo; Moses A. Adegoke; Franklin C. Njoku (Pakistan Journal of Engineering & Technology)
Several epidemics and pandemics have plagued humanity over the years; however, the coronavirus disease 2019 (COVID-19) pandemic revealed humanity's lack of preparedness for epidemics and pandemic outbreaks. Although several approaches have been proposed, designed, and implemented during and post-COVID-19 by researchers to deal with future epidemic outbreaks, there is a need for lightweight technology solutions to develop technology-based contact tracing (TCT) solutions. Quick response (QR) codes can be considered a lightweight technology as they provide environmentally friendly solutions with flexible applications across industries. They also enable contactless interactions and transactions, which is essential for the health and safety of users in the event of an epidemic. To the best of our knowledge, there exists a few pieces of literature that solely discuss and review the QR code-based TCT solutions adopted during the COVID-19 pandemic. As such, this work explores the QR code for its potential and use as a TCT approach. On this premise, this review discusses factors influencing QR code-based CT and further discusses existing QR code-based techniques for mitigating epidemic outbreaks. Additionally, the hybridization of QR code-based techniques with other TCT solutions has limited discussions that solely focus on QR code-based techniques; as such, QR code-based techniques are compared against other technologies adopted for TCT. The review recommends possible solutions to address the challenges in utilizing QR code-based solutions as it concludes the review.